The Effect of Project Based Learning Assisted by Mobile Learning Applications and Learning Motivation on the Competence and Performance of Teachers - Donna Boedi Maritasari; Punaji Setyosari; Dedi Kuswandi; Henry Praherdhiono (AL-ISHLAH: Jurnal Pendidikan, 2022)
One learning model that can be used to improve teachers' quality, pedagogic competence, and personality is the Project Based Learning (PjBL) learning mod-el. The development in this research carried out the Project Based Learning (PjBL) learning model in collaboration with applying the mobile learning model. The use of project-based learning using mobile applications focuses on optimiz-ing teacher performance. The results of this study are: (1) there is an effect of the PjBL strategy assisted by the Mobile Learning Application on the pedagogical competence of teachers. It shows by the significant p-value 0.05; (2) there is an effect of the PjBL strategy assisted by mobile learning on teacher performance which is shown by the significant p-value 0.05; (3) there is an effect of the ped-agogic competence of teachers in students with high motivation compared to low learning motivation shown by the significant difference of p-value 0.05; (4) The average value shows teacher performance for high learning motivation students toward students with low learning motivation with a significant difference with the p-value 0.05; (5) there was an interaction between the implementation of PjBL strategy assisted by mobile learning and high learning motivation on the teacher's pedagogic competence. It can be seen from the significant value of p 0.05; (6) there was an interaction between the implementation of PjBL strategy assisted by mobile learning and high learning motivation on teacher performance from the significant value of p 0.05